Working-class discourses of politics, policy and health: 'I don't smoke; I don't drink. The only thing wrong with me is my health'. (20th April 2017) - Mackenzie, Mhairi; Collins, Chik; Connolly, John; Doyle, Mick; McCartney, Gerry
Abstract : It is known that population health is socially and politically determined. A gap, however, between the evidence and policy (where behavioural approaches dominate) is evident. This study used semi-structured interviews in two deindustrialised areas in Scotland to explore understandings of the causes of (ill)health in local communities. Using Raphael's Discourses of Social Health Determinants (2011), we found that participants typically had highly integrated explanations of health, including vivid articulation of links between politics, policies, deindustrialisation, damage to community fabric and impacts on health. This understanding contrasts with that identified by research elsewhere. We posit explanations for our findings and discuss their implications.